Effects of Otago Exercise Program on postural control ability in elders living in the nursing home: A systematic review and meta-analysis. Issue 11 (17th March 2023) - Kong, Lingyu; Zhang, Xinwen; Zhu, Xinrui; Meng, Lingyue; Zhang, Qiuxia
Abstract : Background: Losing postural control ability and related injuries are of particular concern for elders living in the nursing home (NH). The Otago Exercise Program (OEP) is a multimodal exercise training program initially designed as an individually tailored home exercise for community-dwelling elders, but whether its movement characteristics and exercise intensity meet NH elders' needs still needs to be clarified. This study aimed to determine the effects of the OEP in enhancing postural control ability among elders in the NH. Methods: A systematic literature search of English language databases (Cochrane Library, PubMed, EMBASE, CINAHL, and Web of Science) and Chinese language databases (China National Knowledge Infrastructure, Wanfang, and Chongqing VIP) until 15 April 2022 were performed by 2 reviewers on searching randomized controlled trial (RCT) and non-RCT. A meta-analysis was performed using Review Manager 5.3 software. Continuous data were expressed as mean difference (MD) with 95% confidence intervals (95% CI). Dichotomous data were presented as risk ratios (RRs) with 95% CI. Study methodological quality was assessed according to the Cochrane Handbook for Systematic Reviews of Interventions for RCTs and Risk Of Bias In Non-randomized Studies-of Interventions for non-RCTs by 3 reviewers. Results: Nine studies with 546 participants were included in this review. Two hundred and sixty-nine participants received OEP, and 277 only had conventional exercise training. Compared to the conventional exercise training group, the NH elders in the OEP group have considerably decreased in fall risk (MD = −0.84; 95% CI = −1.17, −0.51; P  < .00001) and positively increased in postural balance (MD = 5.55; 95% CI = 3.60, 7.50; P  < .00001), functional mobility in short-distance (MD = −6.39; 95% CI = −8.07, −4.70; P  < .00001), lower-limb muscle strength (MD = 4.32; 95% CI = 3.71, 4.93; P  < .00001), and health status (risk ratio = 0.35; 95% CI = 0.18, 0.66; P  = .001). Conclusions: Current evidence suggests that OEP is practical and feasible in NH. The nursing personnel can receive sufficient support for maintaining and enhancing these elders' postural control ability, especially during the COVID-19 pandemic.